Retention and pre-colon bioaccessibility of oleuropein in starchy food matrices, and the effect of microencapsulation by using inulin. (February 2018) - Pacheco, Camila; González, Estefanía; Robert, Paz; Parada, Javier
Highlights: Release of oleuropein is affected by processing conditions. Baking generated higher retention. Bioaccessibility pre-colon was lower when oleuropein was microencapsulated by using inulin. Results could be explicated by interaction of molecules with biopolymers like starch. Abstract: Oleuropein is a phenolic compound that is present in fruits and olive tree leaves, which has shown enormous health benefits. This study aimed to assess the effects of the baking and boiling cooking methods and the inclusion of extract of olive leaf and inulin microparticles on oleuropein retention and bioaccessibility in a food matrix. Retention was measured after cooking, and bioaccessibility was measured in cooked samples subjected to in vitro digestion. Our findings showed that oven cooking generated matrices that possess oleuropein retention 15% higher than those presented by food cooked in boiling water, while bioaccessibility at small intestine conditions was 27.5% lower when microparticles, rather than an extract in the starchy matrix, were included, which proves the benefits of using inulin microcapsules to enhance the amount of oleuropein that reaches the colon.